Robot rumble - Dixon, Franklin W.; Burroughs, Scott (New York : Aladdin, 2013)
"Bayport Elementary's annual science fair is here, and Frank, Joe, and their friend Phil are determined to win. But the morning of the fair, Phil discovers that their awesome homemade robot has gone missing!"--Back cover.
3.9
K-3
Keywords: Hardy Boys (Fictitious characters) -- Juvenile fiction; Robots -- Juvenile fiction; Schools -- Juvenile fiction; Hardy Boys (Fictitious characters) -- Fiction; Robots -- Fiction; Schools -- Fiction; Hardy Boys (Fictional characters) -- Fiction; Robots -- Fiction; School stories